DETERMINANTS OF THE CAPITAL STRUCTURE OF EUROPEAN FIRMS: THE MODERATING ROLE OF EFSF/ESM FINANCIAL ASSISTANCE PROGRAMS - Georgios Chatzinas (Universiti Utara Malaysia, 2021)
The present study has investigated the moderating effect of the European Financial Stability Facility (EFSF) / European Stability Mechanism (ESM) support to the firms’ indebtness. Using dynamic panel data, three models were estimated and aimed at the determination of the way that EFSF/ESM financial assistance programs could influence the impact of five firm-specific characteristics, namely growth, profitability, size, tangibility and non-debt tax shield on the capital structure of European firms. Data from 2,086 firms for the period 2003 – 2016 were used, and two dummy variables; one for the EFSF/ESM support period and one for any kind of economic crisis period were formed. The results indicated that pecking order prevailed over trade-off theory. Economic crises did not affect severely the firm-characteristics’ effects, but the EFSF/ESM programs influence appeared in three cases. During the period of EFSF/ESM assistance, profitability’s negative effect on long-term debt ratio disappeared and on total debt ratio strengthened, growth’s positive impact on total debt ratio diminished and non-debt tax shield acquired positive influence on total debt ratio. These changes might be explained by the increased levels of tax rates and decreased levels of uncertainty that the EFSF/ ESM programs caused, as well as by the reluctance of lenders to provide new funds.